Screening for Potential Novel Probiotics With Dipeptidyl Peptidase IV-Inhibiting Activity for Type 2 Diabetes Attenuation in vitro and in vivo - Yan, Fenfen; Li, Na; Yue, Yingxue; Wang, Chengfeng; Zhao, Li; Evivie, Smith Etareri; Li, Bailiang; Huo, Guicheng (Frontiers in Microbiology, 2020)
Diabetes has become the second most severe disease to human health. Probiotics are important for maintaining gastrointestinal homeostasis and energy balance, and have been demonstrated to play positive role in the prevention and treatment of the metabolic syndrome like obesity, inflammation, dyslipidemia and hyperglycemia. The objective of this study was to screen potential anti-diabetic strains in vitro and evaluate its effects in vivo. For the in vitro section, dipeptidyl peptidase IV inhibitory and antioxidant activities of 14 candidate Lactobacillus spp. strains were tested. Then hydrophobicity, acid and bile salt tolerance assays and were determined. The most promising in vitro strain was further evaluated for its anti-diabetic properties in vivo using type 2 diabetes mice induced by high-fat diet and intraperitoneal injection of streptozotocin. The reference strain for this study was Lactobacillus rhamnosus GG. Results showed that cell free excretory supernatants and cell-free extracts of L. acidophilus KLDS1.0901 had better DPP-IV inhibitory activity, antioxidative activities and biological characteristics than other strains. At the end of the treatment, we found that L. acidophilus KLDS1.0901 administration decreased the levels of fasting blood glucose, glycosylated hemoglobin, insulin in serum and AUCglucose, and increased the level of glucagon-likepeptide1 in serum as compared with diabetic mice (p < 0.05). Moreover, L. acidophilus KLDS1.0901 supplementation increased the activities of superoxide dismutase, glutathione peroxidase, the level of glutathione, and reduced the level of malondialdehyde in serum. These results indicated that L. acidophilus KLDS1.0901 could be used as a potential anti-diabetic strain, its applications as food supplements and drug ingredients is thus recommended.